2022
DOI: 10.3389/fnut.2022.791767
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions Associated With the Mexican Diet: Identifying Social Groups With the Largest Carbon Footprint

Abstract: BackgroundMost studies of the climate footprint of diets have been conducted in countries in the global north, but the majority of the world population lives in global south countries. We estimated total dietary greenhouse gas emissions (GHGE) in Mexico, examined the contribution of major food and beverage groups, and assessed variation across social groups.MethodsWe linked individual-level dietary data from the Mexican National Health and Nutrition Survey 2018 to the SHARP Indicators Database, containing GHGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…1.1) Food and nutrient needs, food security, accessibility: P: diet quality, and food needs; S: nutrients and energy requirements. Subsequently, this nutritional-sustainable food guide will be accompanied by a system of equivalent foods (38) that, in addition to incorporating the food's nutrients, will integrate their environmental impact by dietary water footprint (6) , and carbon footprint (7,97) , food prices, and cultural characteristics of the main consumed foods in Mexico (6,12) . https://doi.org/10.1017/S0007114523000843 Published online by Cambridge University Press…”
Section: Intervention Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.1) Food and nutrient needs, food security, accessibility: P: diet quality, and food needs; S: nutrients and energy requirements. Subsequently, this nutritional-sustainable food guide will be accompanied by a system of equivalent foods (38) that, in addition to incorporating the food's nutrients, will integrate their environmental impact by dietary water footprint (6) , and carbon footprint (7,97) , food prices, and cultural characteristics of the main consumed foods in Mexico (6,12) . https://doi.org/10.1017/S0007114523000843 Published online by Cambridge University Press…”
Section: Intervention Functionsmentioning
confidence: 99%
“…The change from the traditional Mexican diet to a Western diet (i.e., increases in animal and ultra-processed foods intake and decreases in the consumption of fruits, vegetables, whole grains, legumes, and nuts), generated by the nutritional transition, has not only propitiated a prevalence of more than 75% of metabolic alterations (obesity, type 2 diabetes, cardiovascular diseases, dyslipidemia) (2)(3)(4) and in the gut microbiota of the Mexican population (5) , but it has also generated the water and carbon footprints of their diet to be among the highest's in the world with more than 8,000 Liters per person per day (L p -1 d -1 ) (6) and 3.9 Kg CO 2 eq p -1 d -1 (7) , respectively. This is linked to the aggravation of climate change, with increases of more than 1.0 ºC in the average atmospheric temperatures since the industrial revolution in the year 1760 (8) and the current water crisis that Mexico is going through, which affects 85% of the territory and has been referred to as the worst water drought in history, affecting the water supply of millions of Mexicans (2,9) .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the principal problem regarding recovering traditional diets is to ensure that the population adheres to these kinds of dietary patterns. Currently, it has been reported that the Mexican population is consuming a Western diet with high environmental implications and detrimental to their health (Aburto et al, 2022; Batis et al, 2021; López-Olmedo et al, 2022).…”
Section: Traditional Diets: the Milpa Dietmentioning
confidence: 99%
“…Similarly, greenhouse gas emissions vary greatly among meat types. Beef, for example, reaches more than 34 CO 2 eq/kg, while the carbon footprint of chicken is 8.58 CO 2 eq/ kg and of fish is 11.62 CO 2 eq/kg (López-Olmedo et al, 2022). Besides, most dietary guidelines widely recommend the intake of nuts as a protein and/or healthy fats source (Armet et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation